Drosophila Piwi functions in Hsp90-mediated suppression of phenotypic variation. - Gangaraju, V.K.; Yin, H.; Weiner, M.M.; Wang, J.; Huang, X.A.; Lin, H. (Nature Genetics, 2011)
Canalization, also known as developmental robustness, describes an organism's ability to produce the same phenotype despite genotypic variations and environmental influences. In Drosophila, Hsp90, the trithorax-group proteins and transposon silencing have been previously implicated in canalization. Despite this, the molecular mechanism underlying canalization remains elusive. Here using a Drosophila eye-outgrowth assay sensitized by the dominant Kr(irregular facets-1)(Kr(If-1)) allele, we show that the Piwi-interacting RNA (piRNA) pathway, but not the short interfering RNA or micro RNA pathway, is involved in canalization. Furthermore, we isolated a protein complex composed of Hsp90, Piwi and Hop, the Hsp70/Hsp90 organizing protein homolog, and we demonstrated the function of this complex in canalization. Our data indicate that Hsp90 and Hop regulate the piRNA pathway through Piwi to mediate canalization. Moreover, they point to epigenetic silencing of the expression of existing genetic variants and the suppression of transposon-induced new genetic variation as two major mechanisms underlying piRNA pathway-mediated canalization.